MY SAY: When will racial demagoguery end? - Abd Razak, Dzulkifli (2008)
As the US presidential race hots up, concerns have been raised that being black could allegedly cost Senator Barrack Obama as much as six percentage points on election day. This is based on a new poll conducted by Stanford University, probing the effect of the Democratic presidential candidate's race on his historic campaign for the White House. "There's a penalty for prejudice, and it's not trivial," Stanford University political scientist Paul Sniderman was quoted as saying. In a close contest, racism "might be enough to tip the election", he adds. Meanwhile, nearly threequarters of the blacks polled say white people have too much influence on US politics. More than 70% of the population in the US is white, while only 13% is black.